2022
DOI: 10.3390/min12070798
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Mechanism of Glycine on the Anatase with Exposed (001) and (101) Facets

Abstract: As a widely existing mineral types on Earth, semiconductor minerals play an important role in the origin of life and the material geochemical cycle. The first step of peptide formation is amino acid adsorption on the mineral surface, but the role and mechanism of different crystal facets of semiconductor minerals are not well understood. Anatase (TiO2) with exposed (001) facets was synthesized by a hydrothermal method, and then analyzed and compared with the purchased ordinary anatase (TiO2) for the adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
2
1
0
Order By: Relevance
“…The low adsorption free-energy value and the rotational mobility of water molecules linked to the O br sites prevent us from identifying a unique adsorption configuration for the M 2 mode (see Supporting Information). We note that this mode might be more dominant by lowering the pH of the solution, as reported in IR adsorption studies. , Overall the low adsorption free energy for this mode is in line with the observation that negatively charged amino acids, at neutral pH, do not guide the peptide adhesion on oxide surfaces in the presence of water ,,,,,, (while it is the contrary for dry conditions).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The low adsorption free-energy value and the rotational mobility of water molecules linked to the O br sites prevent us from identifying a unique adsorption configuration for the M 2 mode (see Supporting Information). We note that this mode might be more dominant by lowering the pH of the solution, as reported in IR adsorption studies. , Overall the low adsorption free energy for this mode is in line with the observation that negatively charged amino acids, at neutral pH, do not guide the peptide adhesion on oxide surfaces in the presence of water ,,,,,, (while it is the contrary for dry conditions).…”
Section: Resultssupporting
confidence: 85%
“…We note that this mode might be more dominant by lowering the pH of the solution, as reported in IR adsorption studies. 61 , 62 Overall the low adsorption free energy for this mode is in line with the observation that negatively charged amino acids, at neutral pH, do not guide the peptide adhesion on oxide surfaces in the presence of water 15 , 16 , 20 , 22 , 25 , 63 , 64 (while it is the contrary for dry conditions).…”
Section: Resultssupporting
confidence: 81%
“…Since Bernal [6] and Goldschmidt [7] proposed the conclusion that "minerals are an important material basis in the origin of life", a large number of scholars have put forward general principles and assumptions in terms of mineral-assisted biosynthesis, and clay minerals are the most common in the specific mineral groups that are cited [3]. Many scholars have used the interaction between clay minerals and amino acids to explore the evolution of early biological macromolecules, but the mechanism is still not fully explained [8]. Hu et al [3] used orthoclase to study the reaction mechanism of amino acid condensation to generate peptide bonds based on density functional theory, analyzed the role of metal ions, surface of orthoclase and amino acid side chains, and concluded that metal ions could catalyze the polymerization of amino acid molecules to generate peptide bonds, amino acid side chains can affect the formation of peptide bonds and the catalytic properties of different ionic systems are significantly different.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the ordinary anatase is composed of a (101) crystal face with a higher surface energy, while a (001) crystal face with a higher reactivity is almost non-existent due to its low surface energy. Liu et al [8] studied the adsorption and mechanism of glycine on anatase with exposed (001) and (101) facets. Pantaleone et al [20] studied the interaction of 11 amino acids with the TiO 2 (101) anatase surface by means of PBE-D2* periodic simulations, both from a static and dynamic point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The most stable and most commonly occurring anatase crystallographic surface is (101) [ 21 ]. In general, ordinary anatase is composed of crystal surfaces (101) with higher surface energy, while crystal surfaces (001) with higher reactivity are almost non-existent due to their low surface energy [ 28 ].…”
Section: Introductionmentioning
confidence: 99%